Special Issue: Advances in the Synthesis of Biologically Important Intermediates/Drugs - Tricia Naicker (Applied Sciences, 2023)
Chemical synthesis is a cornerstone of the development of medicinal chemistry, forming the basis for discovering compounds with new physical and/or biological properties [...]